A 15,800 year record of productivity, carbon accumulation and environmental change at Eight Mile Lake and its catchment, central Alaska - Leah P. Marshall; Darrell S. Kaufman; Nancy H. Bigelow; Matthew S. M. Bolton; Emily C. Cohen; Brooke M. Damon; Bruce P. Finney; Britta J. L. Jensen; Nicholas P. McKay; Meriel J. Medina; Samuel E. Muñoz; Edward A. G. Schuur; et al. (Arctic, Antarctic, and Alpine Research, 2025)
Despite their efficient burial of organic carbon (OC), the role of high-latitude lakes in storing and processing OC under changing climates is poorly understood. We investigate a 15,800 year sedimentary record from Eight Mile Lake, central Alaska, to understand how paleoclimate influenced productivity and OC storage. We compare our data (physical and biogeochemical properties) to data from terrestrial soil cores in the watershed and find three distinct depositional phases. From 15.8–11.7 ka lake sediment accumulated rapidly with the highest OC accumulation rates (OCAR), comparable to Holocene organic-rich soils in the catchment, and promoted by high burial efficiency and enhanced erosion. From 11.7–5.5 ka proportionally more aquatic organic matter accumulated under stable climate conditions. From 5.5 ka – present, lacustrine OCAR was low but with high century-scale variability, suggesting variable erosion and transport with increased moisture, concurrent with loess and organic-rich soil buildup on the hillslope. Our findings demonstrate that factors promoting syngenetic permafrost growth and terrestrial OCAR (primarily temperature and geomorphology) differ from those promoting OCAR in high-latitude lakes (primarily sedimentation rates). Overall, we present a unique pairing of Holocene lake sediment and soil records, highlighting the importance of burial efficiency on OCAR in high-latitude lakes.